SU-8 photoresist as material of optical passive components integrated with analytical microsystemsfor real-time polymerase chain reaction - Walczak, Rafał; Śniadek, Patrycja; Dziuban, Jan A. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
Rapid development of analytical microsystems, also often called as labs-on-a-chip and used to perform various chemical and biochemical analysis with nano- and pico-volumes of the sample, has been observed for almost two decades. Successful application of analytical microsystems in medical and veterinary practices is relevant to many factors but one of them is low price of the disposable microsystem – often in the form of a chip. The chips are made of cheap materials, for example, polymers. One of such material is a negative photoresist SU-8. It is characterized by biocompatibility and possibility of easy fabrication of various three-dimensional fluidic microstructures. Moreover, SU-8 is transparent for visible light. It makes SU-8 attractive material for labs-on-a-chip dedicated for genetic material analysis by real-time polymerase chain reaction (PCR). In this paper, we present the results of investigations of the influence of PCR-like temperature profiling on the transmittance spectra. The autofluorescence effect of SU-8 illuminated with various lasers has also been investigated as one of the factors limiting sensitive fluorescence readout. The results obtained showed that SU-8 can be successfully applied as labs-on-a-chip material but, due to high SU-8 autofluorescence, red-line fluorochromes are preferred when high-sensitivity fluorescence detection is required.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 873-884
Keywords: optyka; SU-8; fluorescence; autofluorescence; microfluidics; lab-on-a-chip; real-time PCR